States of entanglement data in the Irish landscape - Anderson, Sven 1977-; Butler, Alan 1951-; Capener, David ca. 20. Jh; Lally, Donal ca. 20. Jh; Lyster, Clare ca. 20. Jh; McDermott, Fiona (Actar Publishers, 2021)
"The book investigates how data production and consumption territorialize the physical landscape filtered through Ireland's role in global communications and, as told by the Irish Pavilion at the 2021 Venice Architecture Biennale, an installation that focuses on the materiality of data infrastructure in space"--
2106
Keywords: Geschichte 2000-; Datentechnik; Kunst; Energieverbrauch; Landschaft; Irland; Ausstellungskatalog -- Irish Pavillon -- 22.05.2021-21.11.2021 -- Venedig